Implementation of Merdeka Curriculum in Pilot Elementary, Middle, and High Schools in Pontianak Municipality - Gustaf Hariyanto; Lukas Ahen; Semi Semi (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2026)
This study aims to examine how the implementation of the Merdeka Curriculum (MC) in Catholic Religious Education (CRE) is being carried out across some Driving Schools (Elementary, Junior, and High School) in Pontianak Municipality. It also aims to uncover the opportunities and challenges for Religious Education teachers in Driving Schools as they become Driving Teachers. The research method is a qualitative approach, with data collected through interviews and documentation from various stakeholders, including principals, teachers, and the Catholic Institutional Guidance and Counseling of Pontianak Municipality. The results show that implementing the Merdeka Curriculum in the Driving Schools (DS) has presented both challenges and opportunities, such as improving teacher competency and adapting to a more flexible curriculum. However, there are obstacles related to conceptual understanding, resource readiness, and school environmental support. These findings provide important insights into strategies and steps that need improvement to ensure the implementation of the Merdeka Curriculum runs more optimally and has a positive impact on learning quality in the Driving Schools that have been removed from it. This study recommends increasing teacher training and mentoring, and strengthening collaboration between schools, as strategic steps going forward.